Іконографія української народної ікони на склі - Тріска, О. (Інститут народознавства НАН України, 2007)
The article bring review of iconographical repertory of folk icons on glass sheets spread in Bukovina, Hutsul land and Pokutia at the second half of XIX and the first third of XX cc. According to their themes the works are divided into Our Lady’s, Lord’s and hagiographical ones. The creations had been painted after graphical examples or patterns, designed by craftsmen especially for this aim.